2009
DOI: 10.1038/sj.bjc.6605003
|View full text |Cite
|
Sign up to set email alerts
|

Lignans and breast cancer risk in pre- and post-menopausal women: meta-analyses of observational studies

Abstract: Phyto-oestrogens are plant compounds structurally similar to oestradiol, which have been proposed to have protective effects against breast cancer. The main class of phyto-oestrogens in the Western diet is lignans. Literature reports on the effect of lignans in breast cancer risk have been conflicting. We performed three separate meta-analyses to examine the relationships between (i) plant lignan intake, (ii) enterolignan exposure and (iii) blood enterolactone levels and breast cancer risk. Medline, BIOSIS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 60 publications
2
54
0
1
Order By: Relevance
“…In particular, the intake of lignans, which are polyphenolic compounds concentrated in woody portions of plants, seed coats, and the bran layer of grains, has been inversely associated with risk of breast (27) and colon cancer (8, 9). Lignans are converted by the gut microbiota to enterolignans, which are bioactive chemicals found in measurable quantities in plasma and urine.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the intake of lignans, which are polyphenolic compounds concentrated in woody portions of plants, seed coats, and the bran layer of grains, has been inversely associated with risk of breast (27) and colon cancer (8, 9). Lignans are converted by the gut microbiota to enterolignans, which are bioactive chemicals found in measurable quantities in plasma and urine.…”
Section: Introductionmentioning
confidence: 99%
“…148 A recent meta-analysis indicated that these phytohormones may decrease the incidence of breast cancer. 149 The highest production of carcinogens was associated with gut anaerobic bacteria and was lowered by supplementation with live lactobacilli. 150 H. pylori infection of the gastric mucosa was shown to create the conditions for developing ulcers, adenocarcinomas and gastric B-cell lymphomas.…”
Section: Cancermentioning
confidence: 99%
“…37 Lignans have also been shown to favorably influence estrogen metabolism, 38 and high intakes of lignans have been related to decreasing breast cancer risk. [38][39][40] In addition, extra virgin olive oil contains squalene, 41 which has been shown to be a tumor inhibitor. 42 It has been suggested that the squalene content of olive accounts in large part for the association of olive oil with diminished cancer risk.…”
mentioning
confidence: 99%